After the sunset - Ratner, Brett; Brosnan, Pierce; Hayek, Salma, 1966-; Harrelson, Woody; Cheadle, Don; Harris, Naomie, 1976-; Spinotti, Dante; Schifrin, Lalo; New Line Home Entertainment (Firm); Warner Home Video (Firm) ([United States] : New Line Home Entertainment ; Burbank, CA : Distributed by Warner Home Video, 2005)
Two master thieves are finally retiring after one last incredibly succesful heist. Moving to the Bahamas to reside in their own tropical paradise, the pair's old nemesis, FBI Agent Stan P. Lloyd shows up to make sure they really are retired. Docked in the port is a ocean liner called the "Diamond Cruise" and Stan is convinced that they're not really retired at all, and that this is just the next set up. While Lola is busy settling into their new life, Max is contemplating whether or not to steal the famous Napoleon diamond
Title from container
Originally released as a motion picture in 2004
Special features: "Before, during and after the sunset" documentary; "Interview with a jewel thief" documentary; blooper reel; deleted/alternate scenes; DVD-ROM features: content-script to screen
Director of photography, Dante Spinotti ; art director, Steve Arnold ; editor, Mark Helfrich ; music, Lalo Schifrin ; costume designer, Rita Ryack ; production designer, Geoffrey Kirkland ; visual effects supervisor, Stephen Rosenbaum
Pierce Brosnan, Salma Hayek, Woody Harrelson, Don Cheadle, Naomie Harris, Chris Penn, Mykelti Williamson, Obba Babetundé, Russell Hornsby
MPAA rating: PG-13; for sexuality, violence and language
Keywords: Diamonds -- Drama; Robbery -- Drama; Criminal behavior -- Drama; Diamantes -- Teatro; Robo -- Teatro; Spanish language materials; French language materials; Feature films; Video recordings for the hearing impaired; Comedy -- Feature; Adventure -- Feature; Feature films